(untitled) (The Pakistan Development Review, 1998)
Traditionally, cooperatives have been expected to serve a broad set of sociopolitical and economic objectives ranging from self-help and grass-root participation to welfare and distribution, including economies of scale and social control over resource allocation and mobilisation. However, these various objectives are not mutually consistent. There exists substantial trade-off in the realisation of many of these goals. It is therefore necessary to weigh their relative importance in the felt needs and priorities of a particular community at any given point of time if performance of cooperatives is to be evaluated in an appropriate context. An attempt to fulfil a range of these conflicting objectives simultaneously has eventually led to a broad based disenchantment with the cooperative movement.